KORELASI TINGKAT KEBISINGAN DENGAN STRESS KERJA PADA PEKERJA PABRIK BATU ALAM DALAM PERSPEKTIF HUKUM KESEHATAN KERJA - Yani Kamasturyani (IKesT Muhammadiyah Palembang, 2023)
Introduction: Permenkes No. 70 of 2016 concerning Standards and Requirements for Industrial Work Environment Health states that the NAB or Threshold Limit Value is the average intensity of exposure to physical or chemical hazards that can be accepted by all workers without causing health problems or illness at work in a day that does not exceed 8 hours. per day or 40 hours per week. The aim of this research is to determine the relationship between noise levels and work stress in natural stone factory workers in terms of health law. Method: The type of research used in this research is quantitative research with an observational analytical research design and a cross-sectional approach. The population of this study were workers at a natural stone factory in Kepuh village, Cirebon district. The sampling technique used was total sampling. The samples used were all 59 natural stone factory workers in Kepuh village, Cirebon district. Results: The research results show that most factory production areas are noisy (79.7%), factory workers experience as much stress as 76,5% Discussion: The conclusion of the research shows that there is a significant relationship between noise levels and work stress among natural stone factory workers in Kepuh Village, Cirebon Regency with p value = 0.000. The results of the juridical analysis of the relationship between noise levels and work stress among natural stone factory workers from a health law perspective are linked with Industrial Work Environment Health Standards and Requirements (Permenkes No. 70 of 2016) which states that every industry is obliged to meet standards and implement industrial work environment health requirements. The lack of socialization regarding legal regulations has resulted in the non-fulfillment of the noise threshold standards that should exist in the natural stone industry.